Deployable teleradiology Bosnia and beyond. - Levine, B.A (IEEE Transactions on information technology in biomedicine)
The United States military has been an effective proponent of digital imaging and teleradiology. A digital imaging network that eliminates the use of X-ray film makes military medicine requirements simpler. X-ray film requirements include storage of new, unexposed films, storage and use of chemicals and water for processing, and disposal of chemicals. In some deployed situations, the chemical discharge needs to be collected and shipped out of the area. Therefore, the ability to implement electronic imaging and eliminate or greatly reduce the dependence on film, chemicals, and water are intrinsically important to military medicine. In December 1995, the United States government began deployment of 20,000 United States troops to Bosnia-Herzegovina as part of NATO's peacekeeping implementation force (IFOR) operation. A full complement of military medical support facilities was established in Bosnia. An army base in Hungary was the location from which the deployment was staged. The project to deploy telemedicine and teleradiology capabilities to the medical treatment facilities (MTF) in Bosnia and Hungary became known as PrimeTime III. This paper deals with the deployable teleradiology (DEPRAD) system that was installed by the Imaging Science and Information Systems (ISIS) Center, Department of Radiology, Georgetown Medical Center, Washington, DC, at a number of facilities to implement filmless radiology and teleradiology services in support of PrimeTime III.